Brill's companion to Roman tragedy - Harrison, George W. M., 1951- (Brill's Companions to Classical Studies., 2015)
Until the Renaissance the centrality of Roman tragedy in Western society and culture was unchallenged. Studies on Roman Republican tragedy and on Imperial Roman tragedy by the contributors have been directing the gaze of scholarship back to Roman tragedy. This volume has two goals: first, to demonstrate that Republican tragedy had a far more central role in shaping Imperial tragedy than is currently thought, and quite possibly more important than Classical Greek tragedy. Second, the influence of other Roman literary genres on Roman tragedy is greater than has formerly been credited. Studies on von Kleist and Shelley, Eliot and Claus help reconstruct the ancient Roman stage by showing how moderns had thought to change it for contemporary aesthetics.